An evaluation of subsidized rural primary care programs: II. The environmental contexts. - Ricketts, T C (1983)
The placement of subsidized primary care programs in rural communities has been an important aspect of national health policy over the last decade. Using survey and secondary data from programs in over 700 counties in the United States, it was found that while about one-fourth of all counties with some rural populations have been affected by these programs, certain environmental factors are associated with more or less likelihood of placement. High levels of need and low levels of health care resources are positively associated with the presence of a program. States with health policy climates supportive of reimbursement and broader staffing of primary care programs also contained programs in a higher proportion of their rural counties. The effects of decreased federal funding, increased state responsibility, and the precarious market conditions for primary care programs are discussed with emphasis on the mechanisms for developing favorable climates for these programs.